2023
DOI: 10.1002/advs.202206889
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1β Is an Androgen‐Responsive Target in Macrophages for Immunotherapy of Prostate Cancer

Abstract: Great attention is paid to the role of androgen receptor (AR) as a central transcriptional factor in driving the growth of prostate cancer (PCa) epithelial cells. However, the understanding of the role of androgen in PCa-infiltrated immune cells and the impact of androgen deprivation therapy (ADT), the first-line treatment for advanced PCa, on the PCa immune microenvironment remains limited. On the other hand, immune checkpoint blockade has revolutionized the treatment of certain cancer types, but fails to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The specific signal may vary depending on the TME context. For example, there is no evidence of TNF switching in the Hi-MYC GEMM, or in human prostate cancers while in some PTEN-deficient GEMMs, IL1ß triggers myeloid immune suppression (68). However, we propose that the cellular interactions within the TME are likely to be similar in human nmCRPC and mCRPC as well as GEMMs.…”
Section: A Model For the Development Of Crpcmentioning
confidence: 74%
“…The specific signal may vary depending on the TME context. For example, there is no evidence of TNF switching in the Hi-MYC GEMM, or in human prostate cancers while in some PTEN-deficient GEMMs, IL1ß triggers myeloid immune suppression (68). However, we propose that the cellular interactions within the TME are likely to be similar in human nmCRPC and mCRPC as well as GEMMs.…”
Section: A Model For the Development Of Crpcmentioning
confidence: 74%
“…In CRPC, AR signaling remains active despite androgen depletion through ADT. Ligand-independent activation is a mechanism contributing to AR activation in CRPC, wherein alternative signaling pathways bypass the need for androgens 4 6 . Growth factor receptors (e.g., EGFR and IGF-1R) and intracellular signaling cascades (e.g., PI3K/Akt and MAPK) activate AR signaling without androgens.…”
Section: The Ar Signaling Axis In Crpc and Clinical Dilemmamentioning
confidence: 99%
“…Furthermore, ADT has been associated with overcoming the inhibitory effects of AR on IL-1β, thus leading to excessive expression and secretion of IL-1β in TAMs. IL-1β induces MDSC accumulation, thereby inhibiting the activation of cytotoxic T cells and leading to an immune suppressive microenvironment ( Figure 2 ) 4 . Moreover, androgen signaling suppresses T-cell immunity against cancer in males by upregulating the expression of USP18, and consequently inhibiting TAK1 phosphorylation and subsequent activation of NF-κB in antitumor T cells.…”
Section: Crosstalk Between Ar Signaling and Immune Cells Within The Timementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, recent research has revealed a high abundance of macrophages in CRPC tissues ( 3 ). In addition, a high abundance of macrophages can suppress T cell activity, leading to an immunosuppressive microenvironment that promotes castration-resistant progression of PCa ( 9 ). Thus, targeting macrophages has emerged as a potential approach for PCa treatment ( 10 ).…”
Section: Introductionmentioning
confidence: 99%